Produção e uso de proteínas heterólogas quiméricas de flavivírus de circulação nacional para produção de plataformas diagnósticas sorológicas - Samille Henriques Pereira (2023)
Arboviruses constitute a group of viruses transmitted primarily by mosquitoes. They represent a major public health problem worldwide. Among them, Zika virus (ZIKV) and Dengue virus (DENV) stand out. Dengue is the most important arboviral disease in the world, being associated with a significant social and financial burden, outbreaks of this disease occur annually. The arrival of Zika in Brazil (2015) drew attention, because despite being an acute and self-limiting disease, part of the individuals had severe neurological manifestations, congenital complications and Guillain-Barré syndrome. The great antigenic similarity between flaviviruses makes diagnosis difficult. Thus, there is a need to improve diagnostic tools. The objective of this work was to generate chimeric proteins capable of serologically differentiating ZIKV or DENV infections. The recombinant proteins (ZIKV-1, ZIKV-2, ZIKV-3 and DENV- 1) were designed and their respective genes subcloned into a pET21a expression vector. The recombinant proteins were expressed and purified and antigenicity validated, with the exception of DENV-1, which did not was expressed. Purified proteins were tested as solid phase antigens in standard ELISA protocols for detection of anti-ZIKV IgG antibodies. The results obtained after standardization are promising, and the tests elaborated with the recombinant antigens showing high sensitivity and specificity, in addition to low cross-reactivity with the interferent. The ZIKV-1 protein showed 91% sensitivity and 97% specificity, the ZIKV-2 protein showed 95% sensitivity and 96% specificity, and the ZIKV-3 protein showed 66% sensitivity and 84% specificity. Regarding the DENV interferent, there was 10% cross-reactivity for ZIKV-1 and 19% for ZIKV-3, ZIKV-2 did not show cross-reactivity. The assays were also carried out at the “Laboratório de Pesquisa em Virologia” (FAMERP) and presented similar results, demonstrating reproducibility. The results found for ZIKV-1 and ZIKV-2 show great potential for the development of a specific diagnostic test for the detection of IgG antibodies to ZIKV using the produced chimeric proteins.